2003
DOI: 10.1002/joc.961
|View full text |Cite
|
Sign up to set email alerts
|

Winter snow anomaly and atmospheric circulation in Mongolia

Abstract: An observational study was conducted of winter snow anomaly in Mongolia and the associated atmospheric circulation. Monthly data of snow depth and temperature at 23 Mongolian stations from 1940 to 1992 were used for a statistical analysis. The Mongolian snow amount is fairly large in the northern mountainous regions and decreases to the south. On average, there is a substantial seasonal increase in snow depth during November and December. The deepest snow occurs in January, with an average depth of 3.4 cm aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 11 publications
(15 reference statements)
3
55
0
Order By: Relevance
“…Morinaga et al [2003] found a significant and negative correlation between snow depth and the EA/WR pattern in January (R = À0.47). Ye [2001b] analyzed the interannual variability of the winter snow accumulation in northern Eurasia between 1936 and 1995 using rotated PCA and showed a snowpack pattern representative of central Siberia and western Russia, which is connected to the EA/WR pattern.…”
Section: Component 2: Central Siberiamentioning
confidence: 88%
See 1 more Smart Citation
“…Morinaga et al [2003] found a significant and negative correlation between snow depth and the EA/WR pattern in January (R = À0.47). Ye [2001b] analyzed the interannual variability of the winter snow accumulation in northern Eurasia between 1936 and 1995 using rotated PCA and showed a snowpack pattern representative of central Siberia and western Russia, which is connected to the EA/WR pattern.…”
Section: Component 2: Central Siberiamentioning
confidence: 88%
“…[7] Several studies have investigated the links between atmospheric circulation patterns and snow cover and, in some cases, found significant relationships that would be useful for seasonal forecasting [e.g., Saunders et al, 2003;Gutzler and Rosen, 1992;Clark et al, 1999;Morinaga et al, 2003;Bamzai, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Annual average precipitation in this area is less than about 350 mm, but its interannual variation is large (Vandandorj et al 2015;Yu et al 2004), which is typical for drylands. Because precipitation and snowfall increase and temperature decreases from south to north (Morinaga et al 2003;Nandintsetseg and Shinoda 2011), vegetation correspondingly changes from desert to drylands and forest steppe ecosystems. Droughts and severe winters are a cause of high mortality among livestock (Fernandez-Gimenez et al 2012Tachiiri and Shinoda 2012) and wild animals (Kaczensky et al 2011a).…”
Section: Environments Of Mongolia's Gobi-steppe Ecosystemmentioning
confidence: 99%
“…The annual mean temperature is approximately -4 °C in the high mountains, 2 °C in the steppe and desert steppe zones, and 6 °C in the desert regions. Snowfall occurs between mid-October and the end of April, and the annual maximum snow depth (34 mm) occurs in January (Morinaga et al, 2003). The growing season (from May to August) in Mongolia is very short.…”
Section: Study Area and Datamentioning
confidence: 99%